Acquisition Cost of Land and Building Rights Based on Buying and Selling - Singgih Permana Adhi (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2019)
The collection of regional taxes and levies must be based on Law Number 28 of 2009 concerning Regional Taxes and Regional Levies, and for the Banyumas Regency area, it has been regulated in Regional Regulation Number 1 of 2011 concerning Regional Taxes in conjunction with Regional Regulation Number 22 of 2016 concerning Amendments to the Second Regulation Region Number 1 the Year 2011 concerning Regional Taxes. One type of tax that is under the authority of the regions is the Fees for Acquisition of Rights on Land and Buildings, hereinafter referred to as BPHTB. The approach method used in thisresearch is the normative juridical approach method. The data used are secondary data and primary data as a complement to secondary data. The results and discussion are the application of BPHTB based on the sale and purchase of the implementation including the process of filling in the SSPD BPHTB, determining tax objects, tax taxes, calculating taxes, research or validation, and payment. BPHTB is based on the sale and purchase of applications based on the PDRD Law and Regional Tax Regulations, the basis for calculating the BPHTB is the transaction price, therefore based on the Regent Regulation, the RegionalFinance Agency carries out a research procedure (validation) of BPHTB based on buying and selling with the truth of the transaction price value used to calculate BPHTB. PPAT which regulates the deed of transfer of rights, without ta supervision has been paid and validated giving legal consequences for PPAT in the form of sanctions in the form of fines for each award. Law enforcement of sanctions on administrative fines against PPAT and the procedures for its implementation are not regulated and have not been further regulated in the PDRD Law, Regional Tax Regional Regulations, or in implementing regulations.Keywords: Regional Taxes; Fees for Acquisition of Rights on Land and / or Buildings; Legal Consequencesof Land Deed Making Officials.